OPTIMIZATION OF ENZYMATIC HYDROLYSIS OF FISH PROTEIN HYDROLYSATE (FPH) PROCESSING FROM WASTE OF CATFISH FILLET PRODUCTION - Bagus Sediadi Bandol Utomo; Theresia Dwi Suryanigrum; Herbert R Harianto (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2014)
An experiment to determine the optimum condition of fish protein hydrolysate (FPH) processing has been conducted to produce FPH with high protein content. The raw material was catfish (Pangasius sp.) waste from catfish fillet production. Fat content, sensory (color, odor and flavor), total number of bacteria (TPC) and E. coli were analyzed as supporting parameters. The experiment was initiated with preliminary experiment to determine the optimum temperature (temp variation: 50oC, 55oC, 60oC, and 65oC) and concentration of commercial papain enzyme (conc variation: 4%, 6%, and 8%) in FPH hydrolysis, while the main experiment was to determine the optimum time of hydrolysis (time variation: 6, 12, 24, 36, and 48 hours), and pH (pH variation: 5 and 7). Results showed that the optimum temperature in preliminary experiment was 60oC and optimum concentration of enzyme was 4%, whereas the main experiment resulted the optimum hydrolysis time of 48 hours and optimum pH of 5. This condition produced FPH with protein content of 1.21% wet weight basis (wb)  or 39.03% dry weight basis (db) and fat content of 0.16% wb (5.16% db). The sensory analysis of the end product revealed that from max score of 5, the scores of color, odor and flavor of the FPH were 3.50, 2.17 and 2.29, respectively. The product had TPC of 1.1x 107CFU/g with no E. coli infection.